Evaluasi Pengelolaan Penyakit Tanaman Terpadu pada Petani Jagung (Zea mays L.) Di desa Suka Menang, Kecamatan Gelumbang, Kabupaten Muara Enim, Sumatera Selatan - Arsi Arsi; Fitra Nanda Kurnia; Suparman Suparman (Politeknik Negeri Lampung, 2024)
Corn (Zea mays L.) is one of the most important food crop commodities in the world after rice and wheat. In some countries, corn is the main source of carbohydrates. However, pests and diseases are the main obstacles to maize production in the tropics and sub-tropics. There are two main diseases that have the potential to reduce maize production, including leaf rust and leaf blight. leaf rust disease can reduce production up to 70% Leaf rust disease is caused by Puccinia Sp. Leaf blight can cause yield losses of up to 50%. Leaf blight is caused by Helminthosporium turcicum. Therefore, combined control is needed to minimize the impact, namely by applying the concept of integrated disease management. This study aims to determine evaluate integrated disease control that has been carried out by several farmers in Suka Menang village, Gelumbang District, Muara Enim Regency. The results of field practice show that most of the corn farmers in Suka Menang Village, Glummbang District, Muara Enim Regency have implemented the concept of integrated disease management. In the implementation process, farmers are not aware that what they are doing is included in the control. There are 2 types of diseases that attack corn plants, namely, Puccinia sp. and Helminthosporium turcicum.